2016
DOI: 10.5535/arm.2016.40.5.885
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Ultrasound-Guided Interfascial Pulsed Radiofrequency and Ultrasound-Guided Interfascial Injection on Myofascial Pain Syndrome of the Gastrocnemius

Abstract: ObjectiveTo investigate the comparative treatment effects of ultrasound-guided pulsed radiofrequency treatment (UG-PRF) in the gastrocnemius interfascial space and ultrasound-guided interfascial injection (UG-INJ) on myofascial pain syndrome.MethodsForty consecutive patients with myofascial pain syndrome of the gastrocnemius were enrolled and were allocated to one of the two groups. Twenty patients were treated by UG-PRF delivered to the gastrocnemius interfascial space (UG-PRF group) and the other 20 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…This result is in agreement with previous studies, in which PRF has better and longer effects compared to local anesthesia when used on radiculopathy, neuropathy, joint arthritis, or complex regional pain syndrome. [ 17 , 38 40 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This result is in agreement with previous studies, in which PRF has better and longer effects compared to local anesthesia when used on radiculopathy, neuropathy, joint arthritis, or complex regional pain syndrome. [ 17 , 38 40 ]…”
Section: Discussionmentioning
confidence: 99%
“…Eight (66%) out of 12 patients reported more than 50% pain relief at 6 months after the procedure. In 2016, Park et al [ 17 ] evaluated the effect of US-guided PRF stimulation on the interfascial area of the GCM in 20 patients. The NRS score was reduced from 5 to 2.4, and the effect of PRF was sustained for at least 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of RF therapy is to produce a therapeutic effect by damaging the abnormal peripheral nerve of local hyperplasia, separating and releasing the contracture of soft tissue and improving microcirculation[ 55 ]. Several studies have shown that RF treatment of trapezius pain, psoas pain, heel pain and other MPS has a significant effect[ 56 - 58 ]. The complications of RF treatment of MPS include the injury caused by puncture operation.…”
Section: Therapeutic Principles and Methodsmentioning
confidence: 99%